2000
DOI: 10.1046/j.1442-2042.2000.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal masses detected by general health checkup

Abstract: Background: A total of 60 604 persons underwent a general health checkup at Toma Hospital, Saitama, Japan, between January 1993 and June 1997, and transabdominal ultrasonography (US) was performed on all persons. We investigated the usefulness of transabdominal US in detecting renal tumors during general health checkups. Methods: A definite diagnosis was made in cases where the re-examination by US revealed calculus with acoustic shadow or a simple cyst. Computed tomography (CT) was conducted in patients suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…With the aging populations and the increased use of imaging in developed countries, it is reasonable to assume that the issue of appropriate management of small renal masses will become even more important 14, 67. More radiologic examinations are performed in the elderly, with a greater chance of detection of incidental masses.…”
Section: Discussionmentioning
confidence: 99%
“…With the aging populations and the increased use of imaging in developed countries, it is reasonable to assume that the issue of appropriate management of small renal masses will become even more important 14, 67. More radiologic examinations are performed in the elderly, with a greater chance of detection of incidental masses.…”
Section: Discussionmentioning
confidence: 99%
“…The present study highlights the low prevalence of the disease, resulting in low detection rates. Table 2[19–25] compares these rates among different studies; the yield was slightly higher, with 0.33% solid renal tumours and 0.22% confirmed RCC. Only Terasawa et al [20] found a significant yield of RCC (2.6%) using US while screening patients with end‐stage renal disease on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma is also occasionally seen in adolescents and ultrasound in these patients demonstrates an isoechoic or slightly hyperechoic mass 10 . However, contrast‐enhanced CT usually shows a hypervascular rather than heterogeneous cystic and solid mixture as seen in the PNET tumour 11 .…”
Section: Discussionmentioning
confidence: 99%